1999
DOI: 10.1002/(sici)1521-3773(19991102)38:21<3228::aid-anie3228>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis In Vivo byets-1 Antisense Oligonucleotides—Inhibition of Ets-1 Transcription Factor Expression by the Antibiotic Fumagillin

Abstract: The inhibition of angiogenesis in vivo as a result of the inhibition of Ets-1 transcription factor expression by the ets-1 phosphorothioate antisense oligodeoxynucleotide 5'-AGATCGACGGCCGCCTTCAT-3' has been proven by experiments with chicken embryos. Thus, participation of the Ets-1 transcription factor in the formation of new blood vessels in vivo has been demonstrated. Furthermore, it is shown that the angiostatic effect of the fungal metabolite and angiogenesis inhibitor fumagillin is mainly a result of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…Tumour cell proliferation alone is not sufficient for continuous growth of metastases which also requires tumour vascularization (30,56,(67)(68)(69)(70). VEGF is considered the most important factor for tumour vascularization (71).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cell proliferation alone is not sufficient for continuous growth of metastases which also requires tumour vascularization (30,56,(67)(68)(69)(70). VEGF is considered the most important factor for tumour vascularization (71).…”
Section: Discussionmentioning
confidence: 99%
“…However, their action is not restricted to endothelial cells (Rodriguez-Nieto et al, 2001) and some effects have been shown on fibroblasts (Kria et al, 1998). Interestingly, fumagillin was also reported to inhibit Ets-1 expression induced by vascular endothelial growth factor (VEGF) (Wernert et al, 1999). In this context, we investigated the effect of fumagillin on Stromelysin-1 and Ets-1 expression in response to IL-1b and PMA in the HIG-82 cell line.…”
Section: Resultsmentioning
confidence: 94%
“…In the course of this study, we used the fungal antiangiogenic compound fumagillin because of its previously reported ability to downregulate the Ets-1 expression (Wernert et al, 1999). The precise mechanism of action of this drug and its derivatives remains unclear.…”
Section: Stromelysin-1 Promoter Regulation By Endogenous Ets-1 D Bailmentioning
confidence: 99%
“…Fumagillin inhibits the growth of vessels in tumors, and a derivative of the compound has been evaluated in clinical trials as an anticancer drug. The antiangiogenic effect of fumagillin and other inhibitors of MetAP-II have been attributed to the inhibition of the Ets-1 transcription factor expression and the activation of the p53 pathway (5,6). Besides from being anticancer drug targets, MetAPs have the potential to become the target proteins of antibacterial substances because the MetAP functionality is essential for cell growth and bacteria possess only one of the two known MetAP subtypes (7).…”
Section: Methionine Aminopeptidases (Metaps)mentioning
confidence: 96%